A Comparative Analysis of Attitudes Toward Immigrants - Orak, Ugur; Solakoglu, Ozgur (International Journal of Criminology and Sociology, 2016)
The current study examined attitudes toward immigrants in four countries including the United States, China, South Africa, and Turkey, differing from each other by their economic development levels and past immigration experiences. Although considerable attention has been paid to public attitudes toward immigrants, extant research have remained limited to economic and cultural factors as potential determinants of public attitudes, and they have failed to widen the scope of the issue. Thus, they have ignored the role of countries’ past immigration practices and effective immigration policies in shaping natives’ perceptions of immigrants. The current study has added some unique and valuable findings to the literature on attitudes toward immigrants by revealing the distinctive impacts of countries’ past immigration experiences and their immigration policies on natives’ perceptions of immigrants. By using data drawn from the 2015 Global @dvisor Survey, the current study also provided up-to-date research outcomes on the topic.